ANALISIS KONDISI FISIK ATLIT POMNAS CABANG OLAHRAGA BULUTANGKIS MALUKU UTARA TAHUN 2019 - Muliadi Muin; Ardiansyah Nur; Alief Lam Akhmady (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This study aims to determine the physical condition of POMNAS athletes in North Maluku badminton sport in 2019. This type of research is quantitative descriptive. The subjects of this study were all athletes who participated in POMNAS of North Maluku badminton sport as many as 4 people. Data collection techniques using tests and measurements namely physical condition tests which include: a) strength (muscle strength of the fingers, arm and shoulder muscle strength, leg muscle strength, back muscle strength), b) explosive power (arm and shoulder explosive power, leg muscle explosiveness, c) flexibility, d) speed, e) muscle endurance (stomach muscle endurance, arm and shoulder muscle endurance, leg muscle endurance and f) heart-lung endurance. The results of the study illustrate that the average level of physical condition of the North Maluku sports branch of POMNAS in 2019 is in the good category